2021
DOI: 10.1002/2211-5463.13082
|View full text |Cite
|
Sign up to set email alerts
|

Astragaloside IV protects against iron loading‐induced abnormal differentiation of bone marrow mesenchymal stem cells (BMSCs)

Abstract: Iron loading has been reported to be a common stress in the development of cells, and this might be related to bone loss and osteoporosis. Astragaloside IV (ASI‐IV), a pure compound derived from Radix Astragali, has been reported to exhibit cardioprotective, anti‐inflammatory, antioxidant, antiasthmatic and anticancer effects. The aim of this study was to investigate whether ASI‐IV could reverse iron loading‐induced inhibition of cell viability, proliferation, pluripotency and osteogenesis and promote adipogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…After transplantation, BMSCs can migrate to damaged lung tissues, modulate immune cell function, reduce local inflammation, and inhibit fibrosis through various pathways such as paracrine secretion. Astragaloside IV [ 42 ] and astragaloside polysaccharides both promote the proliferation and differentiation of BMSCs after transplantation [ 43 ]. The present study found that the therapeutic effects of AI with and without BMSCs in BLM rats are due to the modulating effects of active Astragalus polysaccharides on BMSCs.…”
Section: Discussionmentioning
confidence: 99%
“…After transplantation, BMSCs can migrate to damaged lung tissues, modulate immune cell function, reduce local inflammation, and inhibit fibrosis through various pathways such as paracrine secretion. Astragaloside IV [ 42 ] and astragaloside polysaccharides both promote the proliferation and differentiation of BMSCs after transplantation [ 43 ]. The present study found that the therapeutic effects of AI with and without BMSCs in BLM rats are due to the modulating effects of active Astragalus polysaccharides on BMSCs.…”
Section: Discussionmentioning
confidence: 99%
“…A study by Cao et al showed that astragaloside IV (AST-IV) helps human BMSCs grow and differentiate into osteogenic cells via the miR-124-3p.1/STAT3 axis. AST-IV is one of the main chemicals that comes from extracts of Astragalus membranaceus [ 60 ] and helps protect and differentiate BMSCs [ 61 ]. AST-IV promotes the cell cycle, viability, and osteogenic differentiation of human BMSCs.…”
Section: Various Signaling Pathways Regulated By Mir-124 In Bonementioning
confidence: 99%
“…Bone marrow mesenchymal stem cells (BMSCs), isolated from the bone marrow of mammals, are an ideal source of MSCs which possess multidirectional differentiation potency 6 . BMSCs have osteogenic differentiation potential, thereby promoting bone formation 7 .…”
Section: Introductionmentioning
confidence: 99%
“…4,5 Hence, finding more effective approaches for promoting bone injury repair is still greatly needed.Bone marrow mesenchymal stem cells (BMSCs), isolated from the bone marrow of mammals, are an ideal source of MSCs which possess multidirectional differentiation potency. 6 BMSCs have osteogenic differentiation potential, thereby promoting bone formation. 7 Increasing evidence…”
mentioning
confidence: 99%